Migration Networks and Location Decisions: Evidence from U.S. Mass Migration - Bryan Stuart; Evan J. Taylor (Institute of Labor Economics (IZA), 2019)
This paper studies how birth town migration networks affected long-run location decisions during historical U.S. migration episodes. We develop a new method to estimate the strength of migration networks for each receiving and sending location. Our estimates imply that when one randomly chosen African American moved from a Southern birth town to a destination county, then 1.9 additional black migrants made the same move on average. For white migrants from the Great Plains, the average is only 0.4. Networks were particularly important in connecting black migrants with attractive employment opportunities and played a larger role in less costly moves.
Keywords: J61; N32; O15; R23; Z13; 330; migration networks; location decisions; social interactions; Great Migration